Convergence Analysis for Variational Inclusion Problems Equilibrium Problems and Fixed Point in Hadamard Manifolds. (4th June 2021) - Chang, Shih-sen; Yao, Jen-Chih; Yang, L.; Wen, Ching-Feng; Wu, D. P.
Abstract: The purpose of this paper is to introduce a new splitting iterative algorithm for finding a common solution of a system of quasi-variational inclusion problems, equilibrium problems and fixed point for quasi-nonexpansive mappings in Hadamard manifolds. It is shown that under mild conditions, the iterative sequence generated by the proposed algorithm converges to a common solution. As applications, we apply our results to study the minimization problems and saddle point problems in Hadamard manifolds.